Association Between Number of Missing Teeth and Hyperlipidemia: The TCLSIH Cohort Study - Qiao F; Guo H; Zhang J; Zhang Q; Liu L; Meng G; Wu H; Gu Y; Song K; Li C; Niu K (Dove Medical Press, 2024)
Feng Qiao,1,2 Hong Guo,1,2 Jing Zhang,1,2 Qing Zhang,3 Li Liu,3 Ge Meng,2 Hongmei Wu,2 Yeqing Gu,2 Kun Song,3 Changyi Li,1 Kaijun Niu2,3 1School of Dentistry, Stomatological Hospital, Tianjin Medical University, Tianjin, People's Republic of China; 2Nutritional Epidemiology Institute and School of Public Health, Tianjin Medical University, Tianjin, People's Republic of China; 3Health Management Centre, Tianjin Medical University General Hospital, Tianjin, People's Republic of ChinaCorrespondence: Kaijun Niu, Nutritional Epidemiology Institute and School of Public Health, Tianjin Medical University, 22 Qixiangtai Road, Heping District, Tianjin, People's Republic of China, Email nkj0809@gmail.com; niukaijun@tmu.edu.cn Changyi Li, School of Dentistry, Stomatological Hospital, Tianjin Medical University, No. 12, Qixiangtai Road, Heping District, Tianjin, 300070, People's Republic of China, Email lichangyi@tmu.edu.cnBackground: To explore the association between the number of missing teeth and the prevalence of hyperlipidemia in a Chinese adult population.Methods: 13,932 adults were investigated in the TCLSIH cohort study. The number of missing teeth was determined at baseline through a self-reported questionnaire, and then classified into three categories: 0, 1- 2, and ≥ 3. We defined hyperlipidemia as total cholesterol (TC) ≥ 5.17 mmol/L or triglycerides (TG) ≥ 1.7 mmol/L or low-density lipoprotein (LDL) cholesterol ≥ 3.37 mmol/L or a self-report of physician-diagnosed hyperlipidemia during follow-up visits. Cox proportional-hazards regression models were employed to assess the relationship between the number of missing teeth and incident hyperlipidemia.Results: A total of 6756 first-incident cases of hyperlipidemia occurred during 42,048 person-years of follow-up (median follow-up, 4.2 years). After adjusted confounders, multivariable HRs and 95% CI for incident of hyperlipidemia across the categories of missing teeth were as follows: in male participants, 1.00 (reference), 1.10 (0.98, 1.22), and 1.03 (0.91, 1.16) (P for trend = 0.30); in female participants, 1.00 (reference), 1.09 (0.99, 1.19), and 1.18 (1.04, 1.33) (P for trend < 0.01).Conclusion: The number of missing teeth is associated with an increased risk of hyperlipidemia in female participants but not in male participants. Systemic chronic inflammation may potentially mediate this association.Keywords: tooth loss, dyslipidemia, epidemiological studies, population health, inflammation